CLASS STRUGGLE AS REFLECTED IN JANE AUSTEN’S PERSUASION: MARXISM PERSPECTIVE - Syafa’ah , Khusnus (2007)
This study concerns with the novel entitled Persuasion, which is written by Jane Austen. The researcher is proposed to analyze a class struggle as reflected in Persuasion based on its structural elements and Marxism perspective . In analyzing the Marxist aspect, the researcher applies the theory of Marxism by Carl Marx.. This research belongs to qualitative research, which employs textual data. The textual data are taken from two resources, namely primary and secondary. The primary data source is the novel itself and the secondary data sources are some books and articles related to the subject.